Analysis of the Effect of Halal Awareness, Subjective Norms, Attitudes and Intentions on Consumer Interest and Use of Halal Cosmetics - Ade Khadijatul Z. HRP; Rahmat Azahar Siregar; Muslim Marpaung; Rahmat (PT Inovasi Pratama Internasional, 2022)
Every Muslim-majority country, including Indonesia, has a growing Muslim population accompanied by rising Muslim incomes. As a result, the demand for halal goods has increased, both in Indonesia and in other countries where the majority are Muslim. Causal association strategy and quantitative approach were used in the research design. Causal relationship means a causal relationship. The quantitative approach is a research method that examines the relationship between variables using numerical data. Halal awareness is the ability to understand, feel, and be aware of events and objects or products that are categorized as halal. The results of this study indicate that there is a significant positive effect of halal awareness on consumer interest, with the obtained value of cr between the effect of halal awareness on consumer interest is 2.423 and p-value = 0.039. Because the value of cr is greater than 1.96 (2.423 > 1.96), and the p-value is less than (0.035 < 0.05). Halal awareness of the Mandailing Natal community is driven by the high religiosity of the community. There is a significant positive influence regarding the effect of halal awareness on consumer interest in the Mandailing Natal community. There is a significant positive effect on the influence of the subjective norm variable on consumer interest in the Mandailing Natal community.